Reducing dark leadership in the public sector: A grounded theory study from Bangladesh - Mahmuda Begum (International Journal of Business and Management (IJBM), 2026)
Dark leadership, the exercise of leadership in ways that produce negative outcomes for followers, teams, and organisations, has received growing scholarly attention, but research remains limited in public sector contexts of the Global South, particularly Bangladesh. This study investigates the causes of dark leadership and examines how internal and external forces shape its context, process, and outcomes within Bangladesh's public sector. Using a grounded theory approach, data were collected through in depth interviews, field notes, and documents from 42 public sector respondents. Analysis identified four causal conditions (political intervention, cultural and social factors, leadership style, and personality), three contextual conditions rooted in dark personality traits (Machiavellianism, narcissism, and psychopathy), and two contextual factors (internal and external forces) that shape how dark leadership emerges and is sustained. The study further identifies a five stage process, spanning situational assessment, resource integration, system development, governance implementation, and monitoring, through which organisations can reduce the emergence of dark leadership, producing five categories of positive outcomes. These findings are integrated into a context specific conceptual framework and substantive theory linking leadership practice to the Sustainable Development Goals. The study offers public sector practitioners and policymakers in Bangladesh, and comparable developing country contexts, a holistic, empirically grounded approach for recognising and mitigating dark leadership, while contributing a Global South perspective to a literature that has been dominated by Western, trait based accounts of destructive leadership.